Enclitic Pronouns In The Anbarāni Dialect Of Talyshi - Avchyan, Hakob («Քոփի Փրինթ» տպ.)
Enclitic pronouns are used in most of New West Iranian languages. They are mainly used for marking the possessor, as well as objects, besides, those Iranian languages and dialects, which show ergative patterns, make use of enclitic pronouns for marking the agent in ergative constructions. This paper deals with the enclitic pronouns and their functions in Anbarāni, one of the Northern Talyshi dialects, spoken in the Islamic Republic of Iran. Where it is possible the features of Anbarāni enclitics will be compared with some other West Iranian languages. Կցական դերանունները գործածվում են ժամանակակից արևմտաիրանական լեզուների մեծ մասում։ Դրանք հիմնականում կիրառվում են մատնանշելու համար հատկացուցչին, ինչպես նաև ուղիղ խնդիրը։ Բացի այդ՝ այն իրանական լեզուներում, որոնք ունեն էրգատիվ համակարգ, կցական դերանունները ցույց են տալիս էրգատիվ նախադասությունների ենթակայի դեմքն ու թիվը։ Այս հոդվածում քննարկվում են Իրանի Իսլամական Հանրապետության տարածքում խոսվող հյուսիսային թալիշերենի Անբարանի բարբառի կցական դերանուններն ու դրանց գործառույթները։
Keywords: Dialectology; Iranian languages; Iranian linguistics